Accounting and analytical support of the efficiency of fixed assets use in managing the efficiency of business processes of the enterprise - Svitlana Shubina; Roman Piskunov; Vitalii Nitsenko; Oleksii Miroshnyk; Daria Pelykh (Фінансово-кредитні системи: перспективи розвитку.)
The system of managing the performance of an enterprise in modern conditions is associated with the risks of entrepreneurial activity and directly depends on high-quality accounting and analytical support, which allows making informed management decisions. Effective management of the formation and use of fixed assets as the main component of the production potential of an enterprise is impossible without the organization of a proper accounting and analytical process and the formation of high-quality management information. Therefore, the issue of organizing accounting and analytical support for the efficiency of use of fixed assets in the managing performance of domestic enterprises under martial law is of a topical nature.